Successful presentations - Mallett, Andrew; Hughes, John. (Oxford : Oxford University Press, 2012)
'Successful presentations is a video course that teaches you how to plan, structure, and deliver presentations in English at work. On the DVD over two hours of material including: interviews with business professionals, expert advice on giving presentations, extracts from business presentations, expert analysis of those presentations.'--Container.
Keywords: English language -- Business English; Business communication; Business presentations